2015
DOI: 10.1098/rspb.2015.0694
|View full text |Cite
|
Sign up to set email alerts
|

Condition-dependent reproductive effort in frogs infected by a widespread pathogen

Abstract: To minimize the negative effects of an infection on fitness, hosts can respond adaptively by altering their reproductive effort or by adjusting their timing of reproduction. We studied effects of the pathogenic fungus Batrachochytrium dendrobatidis on the probability of calling in a stream-breeding rainforest frog (Litoria rheocola). In uninfected frogs, calling probability was relatively constant across seasons and body conditions, but in infected frogs, calling probability differed among seasons (lowest in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 47 publications
3
40
0
Order By: Relevance
“…We have no a priori reason to suspect higher emigration in uninfected frogs or in those with high zoospore burdens compared with those having low burdens (Roznik et al . ). Rather, frogs appeared to maintain calling territories on the stream year‐round suggesting site fidelity (Phillott et al .…”
Section: Discussionmentioning
confidence: 97%
“…We have no a priori reason to suspect higher emigration in uninfected frogs or in those with high zoospore burdens compared with those having low burdens (Roznik et al . ). Rather, frogs appeared to maintain calling territories on the stream year‐round suggesting site fidelity (Phillott et al .…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, previous studies have demonstrated that testes of Bd-infected frogs are larger and contain more sperm than those of uninfected controls [18]. Furthermore, Bd-infected males, when in good condition, are more likely than uninfected males to be callers [19].…”
Section: Discussionmentioning
confidence: 99%
“…Infection risk may be further heightened during mating, as hormonal changes can induce temporary immunosuppression [21]. While social contact seems unlikely to be the primary mode by which the disease spreads [19], H. japonica is a largely terrestrial species so females are unlikely to be exposed to Bd zoospores in standing water except when ovipositing. Whether Bd directly acts on hosts to increase calling behaviour, thereby effectively promoting its own spread, requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…Parasites are usually assumed to be deleterious for their hosts [26,27], and have typically been linked to hosts with poor body condition (e.g. [27,28]).…”
Section: Introductionmentioning
confidence: 99%
“…[27,28]). Body condition is a key parameter for fisheries management [29,30], as it can act as a proxy for predicting future fish growth and reproductive success [31].…”
Section: Introductionmentioning
confidence: 99%